Influence of revegetation on soil microbial community and its assembly process in the open-pit mining area of the Loess Plateau, China - Chang, Yuanyuan; Chen, Fu; Zhu, Yanfeng; You, Yunnan; Cheng, Yanjun; Ma, Jing (Frontiers in Microbiology, 2022)
Vegetation recovery is an important marker of ecosystem health in the mining area. Clarifying the influence of vegetation recovery on the characteristics of soil microbial community and its assembly process can improve our understanding of the ecological resilience and self-maintaining mechanism in the open-pit mining area. For this purpose, we employed MiSeq high-throughput sequencing coupled with null model analysis to determine the composition, molecular ecological network characteristics, key bacterial and fungal clusters, and the assembly mechanism of the soil microbial communities in shrubs (BL), coniferous forest (CF), broad-leaved forests (BF), mixed forest (MF), and the control plot (CK, the poplar plantation nearby that had been continuously grown for over 30 a without disturbance). The results showed that the vegetation restoration model had a significant influence on the α-diversity of the microbial community (P < 0.05). Compared with CK, Sobs and Shannon index of MF and CF have increased by 35.29%, 3.50% and 25.18%, 1.05%, respectively, whereas there was no significant difference in the α-diversity of fungal community among different vegetation restoration types, Actinobacteria, Chloroflexi, Proteobacteria, and Acidobacteria were the dominant phyla. The diversity of the first two phyla were significantly higher than those of CK. However, the diversity of the last two phyla were dramatically lower than those of CK (P < 0.05). Ascomycota and Basidiomycota were dominant phyla in the fungal community. The abundance and diversity of Ascomycota were significantly higher than those of CK, while the abundance and diversity of the latter were considerably lower than those of CK (P < 0.05). The stochastic process governed the assembly of the soil microbial community, and the contribution rate to the bacterial community construction of CK, CF, BF and MF was 100.0%. Except for MF, where the soil fungal community assembly was governed by the deterministic process, all other fungal communities were governed by the stochastic process. Proteobacteria and Acidobacteria are key taxa of the bacterial network, while Mortierellales, Thelebolales, Chaetothyriales and Hypocreales are the key taxa of the fungal network. All these results might provide the theoretical foundation for restoring the fragile ecosystem in global mining region.